2017
DOI: 10.1186/s13063-017-2021-5
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Oxygen during Cardiac Surgery (ROCS) trial: study protocol for a randomized clinical trial

Abstract: BackgroundAnesthesiologists administer excess supplemental oxygen (hyper-oxygenation) to patients during surgery to avoid hypoxia. Hyper-oxygenation, however, may increase the generation of reactive oxygen species and cause oxidative damage. In cardiac surgery, increased oxidative damage has been associated with postoperative kidney and brain injury. We hypothesize that maintenance of normoxia during cardiac surgery (physiologic oxygenation) decreases kidney injury and oxidative damage compared to hyper-oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…To that end, we are currently conducting a clinical trial to further study this mechanism by randomly assigning cardiac surgery patients to intraoperative normoxia or hyperoxia and assessing for oxidative damage and organ injury. 50 This study has noteworthy strengths and limitations. Specifically, trained research staff prospectively collected delirium outcomes in the setting of a clinical trial; we measured markers of oxidative damage, neuronal injury, and blood-brain barrier disruption at numerous perioperative time points representing nearly 4,000 samples; and the large cohort included multiple types of cardiac surgery, increasing the generalizability of the results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To that end, we are currently conducting a clinical trial to further study this mechanism by randomly assigning cardiac surgery patients to intraoperative normoxia or hyperoxia and assessing for oxidative damage and organ injury. 50 This study has noteworthy strengths and limitations. Specifically, trained research staff prospectively collected delirium outcomes in the setting of a clinical trial; we measured markers of oxidative damage, neuronal injury, and blood-brain barrier disruption at numerous perioperative time points representing nearly 4,000 samples; and the large cohort included multiple types of cardiac surgery, increasing the generalizability of the results.…”
Section: Discussionmentioning
confidence: 96%
“…Four hundred patients comprised the cohort. The median (10th percentile, 90th percentile) age of patients was 67 (50,81) yr, 32.8% were female, 30.8% were diabetic, and 70.8% had CPB during surgery (table 1). One hundred-nine patients (27.3%) developed postoperative delirium for a median of 1.0 (0.5, 3.0) days.…”
Section: Patient Characteristics and Deliriummentioning
confidence: 99%
“…A recent meta-analysis based on 12 randomized controlled trials (RCTs) showed the minimal effect of hyperoxia on organ dysfunction, length of hospital stay, and mortality in adult cardiac surgery (26). An ongoing study is currently comparing the increase in serum creatinine in hyperoxygenated patients (FiO 2 of 100%) and those undergoing physiological oxygenation (27).…”
Section: Fio 2 Managementmentioning
confidence: 99%
“…All these factors involve an increased risk of lung injury in thoracic surgery with OLV, ranging from mild to severe acute respiratory distress syndrome (ARDS), and, consequently, an increase of mortality and morbidity (21).…”
Section: One-lung Ventilation (Ovl)mentioning
confidence: 99%
“…The use of a normoxemia strategy did not diminish myocardial damage, nor did it influence secondary outcomes such as cardiac index, systemic vascular resistance index, creatinine, and lactate (30). Another study, aiming to compare the creatinine increase in hyperoxygenated patients (1.0 FiO 2 ) and those undergoing physiological oxygenation, is still underway (21).…”
Section: Protective Ventilation During Cardiac Surgerymentioning
confidence: 99%